2001
DOI: 10.1007/s001980170088
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Changes in Bone and Calcium Metabolism Following Hip Fracture in Elderly Patients

Abstract: Although hip fracture is one of the most common causes of acute immobilization in elderly patients, little is known about the influence of immobilization on changes in bone and calcium metabolism following this event. We therefore compared serum biochemical indices of bone and calcium metabolism in 20 elderly subjects with hip fracture with those measured in 20 healthy age-matched controls. Rankin scores, a measure of functional dependence with 0 representing independence and 5 representing total dependence, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Previous studies showed increased levels of markers of bone resorption in patients with vertebral or hip fractures at an early stage of fracture healing [21], [22], although biochemical markers of bone formation increased at a later stage [23]. Our study showed interesting variations in the levels of the markers of bone metabolism that have not been described in the literature before.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies showed increased levels of markers of bone resorption in patients with vertebral or hip fractures at an early stage of fracture healing [21], [22], although biochemical markers of bone formation increased at a later stage [23]. Our study showed interesting variations in the levels of the markers of bone metabolism that have not been described in the literature before.…”
Section: Discussionsupporting
confidence: 63%
“…(13) Rapid bone loss has also been reported in patients immobilized for prolapsed intervertebral disc, (14) after a stroke, (15) and in premenopausal women who are less physically active. (16) Most of these studies have measured BMD, not bone turnover, or used older, less specific markers of bone metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…(16) Most of these studies have measured BMD, not bone turnover, or used older, less specific markers of bone metabolism. (9,10,(12)(13)(14)(15)(16)(17) The changes in bone turnover after acute immobilization are considered to be mediated through the local and systemic effects of cytokines and hormonal regulators of bone and calcium metabolism, which may be modulated through the activity of the mechanoreceptors in bone. (18)(19)(20)(21) The effects of more modest reductions in mobility on bone turnover have been less well studied.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in BMD correlated with the level of physical activity, ICTP, and age. Because frail patients older than 70 y of age are immobile, they are not able to decrease bone resorption and increase bone mass when treated with calcium and vitamin D. The importance of sufficient mechanical loading has been shown in clinical trials; the effect of intervention with calcium and vitamin D is reduced if patients are immobile (29,30).…”
Section: Discussionmentioning
confidence: 99%